What does economic history teach us? 12 conversations for difficult times - Grata, Paweł; Kinal, Jarosław (Rzeszów University Press, 2025)
This publication is a transcript of conversations conducted and published by the University of Rzeszow in the course of the project “What does economic history teach us? 12 Conversations for Difficult Times” within the framework of the Ministry of Science and Higher Education's ‘Social Responsibility of Science’ program. The talks were attended by prominent economic historians, who answered a number of fundamental questions about the conclusions for the modern world arising from the past. Conclusions that are particularly relevant in the context of the crises that have regularly appeared in recent years, at the same time, conclusions that are extremely relevant in terms of the recommendations for the present and future that flow from the experience of the past. Each of the conversations was a real intellectual adventure, and our excellent interlocutors, whom we sincerely thank at this point, were (in alphabetical order): Prof. Dr. Piotr Franaszek (Jagiellonian University in Cracow), Dr. Joanna Jaroszyk Adam Mickiewicz University in Poznan), Prof. Dr. Slawomir Kamosinski (Kazimierz Wielki University in Bydgoszcz), Dr. Kamil Kowalski (University of Lodz), Dr. hab. Cecylia Leszczynska, prof. UW (University of Warsaw), prof. dr. Wojciech Morawski (Warsaw School of Economics), prof. dr. Andrzej Pieczewski, prof. UŁ (University of Lodz), dr. Krzysztof Popinski (Wroclaw University of Economics).
Keywords: economic history; social history; education; interviews; economy